L’appropriation de la posture d’accompagnement comme fondement de la formation des enseignants de philosophie - Jacques Le Montagner (Recherches en Éducation)
Traditionally, the Institution focuses the teaching training in philosophy on she contents to transmit to the students in a logical way of teaching. Without under estimating the indispensable and important contribution of this training session, we assume that developing a professional didactic centered around the coaching how to philosophy for the students in their last year at high school, can be, for the acquisition of real skills as for their success, a relevant choice. What training devices are likely to favor the gradual construction of this ability of coaching? In what way can the current training of teachers help or hinder this acquisition? What devices, what methods can we use to optimize the transformation of the former methods of teaching of philosophy teachers?